Rare earth element behaviour in seawater under the influence of organic matter cycling during a phytoplankton spring bloom – A mesocosm study - Mara Sutorius; Corinna Mori; Janek Greskowiak; Lea Boettcher; Carina Bunse; Thorsten Dittmar; Thorsten Dittmar; Leon Dlugosch; Nils Hendrik Hintz; Meinhard Simon; Meinhard Simon; Maren Striebel; et al. (Frontiers in Marine Science, 2022)
Rare earth elements (REEs) are used as powerful proxies for a variety of oceanic processes. The understanding of their biogeochemical behaviour in the marine environment is therefore essential. While the influence of OM-cycling on REE patterns in seawater is considered as insignificant, it has been shown that algae and bacteria provide good sorption surfaces for REEs and that components of the dissolved OM pool are able to complex REEs, thus potentially altering their behaviour. To investigate the impact of bio-associated processes on REEs in the bio-productive marine environment, we conducted an indoor mesocosm experiment that mimicked a phytoplankton spring bloom in the neritic coastal North Sea. The incubation period of 38 days covered two distinct phytoplankton bloom phases (diatoms followed by Phaeocystis sp.) and an interjacent bacterioplankton maximum. All dissolved REEs (dREEs) except samarium showed similar temporal concentration patterns, which were closely connected to the bloom succession. The concentration patterns were shaped by the ‘phytoplankton-shuttle’, which summarizes adsorption processes on phytoplankton-derived particulate OM (POM) and resulted in decreasing dREE concentrations alongside chlorophyll-a and POM maxima. The ‘heterotrophic-shuttle’ resulted in increasing dREE concentrations likely linked to heterotrophically mediated regeneration of POM and associated desorption processes. The effect of these processes on dREEs resulted in enhanced fractionation of light REEs (LREEs) relative to heavy REEs (HREEs) during adsorption processes and decreased fractionation as a result of desorption. At times of high dissolved organic carbon (DOC) concentrations, we observed a stabilization of especially dHREEs likely in organic complexes. To test the potential influence of DOC on dREEs, we used a PHREEQC model approach that revealed dREE complexation with components of the DOC pool and an increase in complexation with atomic mass of the REEs. That is, at high DOC concentrations OM-dREE complexation leads to an effective and preferential buffering of dHREE against adsorption. Our findings reveal that OM-cycling influences concentration patterns of dREEs via ad- and desorption processes as well as organic complexation with parts of the OM pool, suggesting these processes can have a significant impact on dREE concentrations in the natural marine environment under high OM conditions.